A multicentric consortium study demonstrates that dimethylarginine dimethylaminohydrolase 2 is not a dimethylarginine dimethylaminohydrolase - Ragavan, Vinitha N.; Nair, Pramod C.; Jarzebska, Natalia; Angom, Ramcharan Singh; Ruta, Luana; Bianconi, Elisa; Grottelli, Silvia; Tararova, Natalia D.; Ryazanskiy, Daniel; Lentz, Steven R.; Tommasi, Sara; Martens-Lobenhoffer, Jens; et al. (Nature Communications, 2023)
Dimethylarginine dimethylaminohydrolase 1 (DDAH1) protects against cardiovascular disease by metabolising the risk factor asymmetric dimethylarginine (ADMA). However, the question whether the second DDAH isoform, DDAH2, directly metabolises ADMA has remained unanswered. Consequently, it is still unclear if DDAH2 may be a potential target for ADMA-lowering therapies or if drug development efforts should focus on DDAH2’s known physiological functions in mitochondrial fission, angiogenesis, vascular remodelling, insulin secretion, and immune responses. Here, an international consortium of research groups set out to address this question using in silico, in vitro, cell culture, and murine models. The findings uniformly demonstrate that DDAH2 is incapable of metabolising ADMA, thus resolving a 20-year controversy and providing a starting point for the investigation of alternative, ADMA-independent functions of DDAH2.
CRIS-Team Scopus Importer:2023-06-30